Thermal Conversion of Municipal Biowaste Anaerobic Digestate to Valuable Char - Roberto Nisticò; Federico Guerretta; Paola Benzi; Giuliana Magnacca; Davide Mainero; Enzo Montoneri (Resources, 2019)
The municipal biowaste anaerobic digestate of a typical waste treatment plant is pyrolyzed under a mild condition (i.e., 540 °C) to directly yield N-doped biochar without performing any subsequent functionalization process. The results confirmed the integration of nitrogen heteroatoms within the carbonaceous framework. The morphological characterization, instead, evidenced the formation of a rather dense biochar with a very low surface area.